'Are they just gonna reject me?' Male adolescents with autism making sense of anxiety: An Interpretative Phenomenological Analysis. (December 2018) - Acker, Louise; Knight, Matthew; Knott, Fiona
Highlights: The lived experience of anxiety was explored with male adolescents with autism, using Interpretative Phenomenological Analysis. Findings demonstrate some typical concerns during adolescent years, such as a wish for social affiliation and worry about academic pressures. However, participants' accounts also highlight how differences commonly seen in autism, such as in sensory processing, might be linked to or exacerbate anxiety during adolescence. The study gains insight into participants' resilience and resourcefulness in navigating these challenges. Some participants managed their anxiety in creative ways, such as through role-play or fantasy. This could provide new avenues for support. Abstract: Background: Anxiety can be a significant difficulty for people with autism, and rates increase during childhood and early adolescence. Nevertheless, little is known about the subjective experience of anxiety in this population. This study aimed to explore this phenomenon using a method conducive to gaining richer insight into participants' lived experiences. Method: This study used Interpretative Phenomenological Analysis to explore the lived experience of anxiety, in 14 male adolescents (aged 13–18 years) with autism. Results: Participants described anxiety which in some ways resembled typically developing adolescent concerns, such as a desire to belong and feel connected to others, and stress linked to academic pressure. However, they also described how their anxiety could be further compounded by qualities that are characteristic of autism, such as difficulty knowing what others felt and how to comfort them, difficulty regulating emotions and the challenge of sensory sensitivities. Some managed their anxiety in ways that might differ from the typically developing population, for example through use of fantasy and role-play. Participants also outlined details about the format and nature of support that they found most helpful. Conclusions: Themes highlight participants' sensitivity and vulnerability in their unique struggle during this time of adolescence, as well as their resilience and resourcefulness in navigating this. A compassionate response is required from health and education professionals, which considers these young people's human need to feel socially connected, which is sensitive to the way that support is provided, and perhaps makes greater use of creative means of intervention (such as involving fantasy and role-play).